2014
DOI: 10.1097/jto.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Sample Features Associated with Success Rates in Population-Based EGFR Mutation Testing

Abstract: EGFR mutation testing should be attempted in any specimen, whether histologic or cytologic. Samples should not be excluded from testing based on TTF-1 status or histologic features. Pathologists should report the amount of available tumor for testing. However, suboptimal samples with a negative EGFR mutation result should be considered for repeat testing with an alternate sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 45 publications
4
105
0
Order By: Relevance
“…As previously established, the rate of EGFR mutations is markedly higher in Asians compared with other ethnic groups such as Caucasian (49,50). Consequently, we suggested that VeriStrat classification might be more useful to identify patients with primary or secondary resistance to EGFR-TKIs, while the classification model in the present study may focus on EGFR-TKI-sensitive populations.…”
Section: Discussionmentioning
confidence: 64%
“…As previously established, the rate of EGFR mutations is markedly higher in Asians compared with other ethnic groups such as Caucasian (49,50). Consequently, we suggested that VeriStrat classification might be more useful to identify patients with primary or secondary resistance to EGFR-TKIs, while the classification model in the present study may focus on EGFR-TKI-sensitive populations.…”
Section: Discussionmentioning
confidence: 64%
“…Archival tissue serves as excellent material for further tumour testing, and such samples are currently used for almost all predictive and prognostic biomarker testing across tumour sites 42 .…”
Section: Molecular Testing: Pathology Perspectivesmentioning
confidence: 99%
“…Specimens with high tumour cellularity, even if they are small, are preferred for molecular testing over those with low tumour cellularity 45,47 . Whenever possible, the entire block and unused precut slides, rather than recut slides, should be sent for molecular testing.…”
Section: Pathology Perspectivesmentioning
confidence: 99%
“…In addition to determining malignancy, lung origin, and pathologic subtype, pathologists evaluate diagnostic specimens to ensure that samples meet the criteria for molecular analysis. Whether cytology or biopsy specimens are obtained, tumour cellularity is the key determinant of the likelihood of successful molecular testing [45][46][47][48] ; both techniques can potentially yield adequate material for diagnostic molecular tests 49 . With respect to cytology specimens, preparation of a cell block is still preferred 24,50 , but other specimens are also suitable for analysis 27 .…”
Section: Pathology Perspectivesmentioning
confidence: 99%